2019
DOI: 10.3390/gidisord1040032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gastric Emptying in Symptoms of Gastroparesis

Abstract: The symptoms of gastroparesis, such as nausea, vomiting, postprandial fullness, early satiety and abdominal pain, frequently impair the quality of life of the affected individuals. The diagnosis of gastroparesis is made after structural etiologies are ruled out and an assessment of gastric function shows delayed gastric emptying. The role of the delay in gastric emptying in the pathogenesis of symptoms of gastroparesis has been debated, with some studies suggesting an association between delayed gastric emptyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 80 publications
0
17
1
Order By: Relevance
“…It is noteworthy that domperidone, a promotility agent and D 2 receptor antagonist, has also demonstrated inconsistent results with respect to its ability to accelerate gastric emptying, with a recent meta‐analysis noting that, based on available studies, domperidone did not exert a significant effect on gastric t 1/2 31,47,51 . The absence of an effect on gastric emptying in this study is therefore not entirely unexpected, and alternative measures of gastric emptying, such as scintigraphy, may be required to confirm the observations of the gastric emptying breath test, as previous studies have demonstrated there is good correlation between scintigraphy and breath test methods of assessing gastric emptying 1,52,53,54 …”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…It is noteworthy that domperidone, a promotility agent and D 2 receptor antagonist, has also demonstrated inconsistent results with respect to its ability to accelerate gastric emptying, with a recent meta‐analysis noting that, based on available studies, domperidone did not exert a significant effect on gastric t 1/2 31,47,51 . The absence of an effect on gastric emptying in this study is therefore not entirely unexpected, and alternative measures of gastric emptying, such as scintigraphy, may be required to confirm the observations of the gastric emptying breath test, as previous studies have demonstrated there is good correlation between scintigraphy and breath test methods of assessing gastric emptying 1,52,53,54 …”
Section: Discussionmentioning
confidence: 46%
“…While gastric emptying is the hallmark for the diagnosis of gastroparesis, there may be various other mechanisms which produce and influence gastroparesis symptoms. 52 A significant increase in volume to fullness with the trazpiroben 25 mg dose was observed, which may explain the trend in American Neurogastroenterology and Motility Society Gastroparesis Cardinal Symptom Index-Daily Diary symptom scores; particularly patient-rated overall severity scores, for which the response appeared to correlate reciprocally with dose. The mechanism for the positive effect of the drug on volume to fullness may be related to the previously documented reduction in upper gastrointestinal symptoms with dopaminergic antagonists, which led to participants' ability to tolerate a greater volume of the nutrient drink.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Importantly, the investigators acknowledge that since some patients did not symptomatically improve after pyloric intervention, this finding reinforces the concept that pyloric dysfunction is not the sole factor in the etiopathogenesis of gastroparesis. Other mechanisms of action that may affect gastroparesis symptoms include "impaired gastric accommodation, hypersensitivity, and extragastric transit abnormalities" [12].…”
mentioning
confidence: 99%